DeNOxing the air in urban spaces by building and construction photocatalytic coverings - J. Fernández-Pampillón; M. Palacios; L. Núñez; M. Pujadas (City and Environment Interactions)
A variety of air depolluting TiO2-based marketed products were applied on bituminous mixtures, sidewalk pavements and facades, giving NOx oxidation ratios under ISO 22197–1:2007 in the 35–9%, 56–2% and 28–2% ranges, respectively. Correspondingly, DeNOx toxicity indexes varied from −0.8 to 5.6, 0 to 14 and −4 to 1 μmol.The three most efficient photocatalytic products were selected: two TiO2-water dispersions, for road and sidewalk, and a TiO2-covering, for facade. NOx purifying ability of these materials were evaluated when key physical parameters were modified. The observed NOx conversion is positively correlated with UV-A irradiance up to 10 W/m2, reaching a plateau, and negatively correlated with relative humidity, with a more pronounced decrease above 35%. Inversely, no dependence with inlet NOx concentration is observed in the range of 0.14–1 ppmv.Further, two first-order kinetic approximations were followed to calculate NO surface deposition rates, giving 2 to 8 10−3 m/s on the selected photocatalytic urban surfaces. Subsequently, the potential NOx sink effect induced in a photocatalytic urban canyon and a NOx-purifier was modelled taking NOx surface deposition rates from 10−3 to 10−1 m/s. Purifying devices could be utilised as a preferred option to help alleviate local atmospheric NOx in high-polluted areas.